Теоретические аспекты реформирования денежно-кредитных отношений - Коробов, Ю.И. (Культура народов Причерноморья, 2013)
В статье дается характеристика процессов реформирования денежно-кредитных отношений с субъективной и объективной стороны. Субъективная сторона включает конкретные мероприятия по реформированию денежной либо банковской системы. Объективная сторона включает совокупность экономических законов, определяющих направление развития денежно-кредитных отношений (общеэкономические законы, законы денег, законы кредита). Условием успешного осуществления реформ является обязательный учет объективных законов. У статті дається характеристика процесів реформування грошово-кредитних відносин з суб'єктивної та об'єктивної сторони. Суб'єктивна сторона включає конкретні заходи з реформування грошової чи банківської системи. Об'єктивна сторона включає сукупність економічних законів, що визначають напрямок розвитку грошово-кредитних відносин (загальноекономічні закони, закони грошей, закони кредиту). Умовою успішного здійснення реформ є обов'язковий облік об'єктивних законів The article describes the process of reforming the monetary relations from the subjective and objective view point. The subjective aspect includes the specific measures to reform monetary or banking system. The article provides an overview of monetary and banking reforms in Russia. The objective aspect includes a set of economic laws determining the development of monetary relations (general economic laws, money laws, credit laws). The paper shows the influence of each of these three groups of laws on the development of money and banking system. The author puts forward the hypothesis of the existence of such objective laws of monetary relations as the law of the demonetization of precious metals, the law of loss of material value of money, the law of the development of credit relations. The author points out that the negative results of reforms of monetary and credit relations in the Soviet period were related to the violation of requirements of objective laws. In order to be successfully implemented all the reforms are required to meet these standards.